HIGHLIGHTING LEARNING COMMUNICATION IN THE INDUSTRIAL ERA 4.0 USING VCLASS MEDIA IN NURDIN HAMZAH UNIVERSITY COMMUNICATION SCIENCE STUDY PROGRAM - Muhaimin - - (INNOVATIO: Journal for Religious Innovations Studies, 2023)
The current era of education is influenced by the industrial revolution 4.0, in which the cyber system is a type of learning environment that uses digital technologies. The learning process takes place by utilizing communication technology that can carry out all work activities through applications that can help them online. One of the applications used is a virtual class (Vclass), with virtual class lecturers and students can carry out learning activities anywhere. Through these applications, lecturers can deliver learning materials in various forms, such as videos, PowerPoint presentation documents (PPT), scientific journal links, electronic books (ebooks), etc. However, implementing online learning still has several obstacles because lecturers cannot meet face-to-face to monitor the learning process, so the expected results are not as desired. The purpose of this study is to describe how learning communication in the industrial era 4.0 describes the obstacles and barriers to online learning. This research uses a qualitative approach with descriptive methods, data collection using observation, interviews, and documentation techniques. The number of samples is ten people. The results of the analysis show that learning communication efforts are carried out using virtual class (Vclass) media, namely: Social presence, Cognitive load, Visualization, and interaction type. At the same time, the obstacles and barriers are that the learners cannot manage time appropriately to complete learning tasks and the limitations of using learning materials independently to understand lecture material. Abstrak: Era pendidikan saat ini dipengaruhi oleh revolusi industri 4.0 yang bercirikan pemanfaatan teknologi digital dalam proses pembelajaran yang dikenal dengan sistem siber (cyber system), proses pembelajaran berlangsung dengan memanfaatkan teknologi komunikasi yang dapat melakukan semua aktivitas pekerjaan melalui aplikasi yang dapat membantu mereka secara online, salah satu aplikasi yang digunakan adalah virtual class (Vclass), dengan virtual class dosen dan mahasiswa dapat melakukan aktivitas belajar dimana saja, lewat aplikasi tersebut dosen dapat menyampaikan materi pembelajaran dalam berbagai bentuk seperti video, dokumen presentasi power poin (PPT), link jurnal ilmiah, electronic book (ebook) dan lain sebagainya. Namun pelaksanaan pembelajaran secara online tersebut masih memiliki beberapa kendala karena dosen tidak bisa bertatap muka secara langsung untuk memonitoring proses pembelajaran sehingga hasil yang diharapkan tidak sesuai dengan keinginan. Tujuan dari penelitian ini adalah mendeskripsikan bagaimana komunikasi pembelajaran di era industri 4.0, mendeskripsikan kendala dan hambatan pembelajaran online. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, pengumpulan data menggunakan teknik observasi, wawancara, dan dokumentasi. Jumlah sampel 10 orang. Hasil analisis menunjukkan bahwa upaya komunikasi pembelajaran dilakukan menggunakan media virtual class (Vclass) yaitu: Sosial presence, Cognitive load, Visualisasi, tipe interaksi. Sedangkan kendala dan hambatan adalah para pembelajar tidak mempu mengelola waktu secara tepat untu menyelesaikan tugas pembelajaran dan keterbatasan menggunakan materi pembelajaran secara mandiri untuk memahami materi perkuliahan.Keywords: Komunikasi Pembelajaran, Media V Class, Era Industri 4.0